SECULARIZATION IN THE MIND OF MUSLIM REFORMISTS: A Case Study of Nurcholish Madjid and Fouad Zakaria (JOURNAL OF INDONESIAN ISLAM, 2007)
Nurcholish Madjid (Indonesia) and Fouad Zakaria (Egypt) represent the two most influential Muslim thinkers concerned with the issue of secularization. This article is a comparative analysis of their ideas, which have triggered intellectual debate on the term “secularization” and its implications in the Muslim world over the last three decades. Positing the discourse on secularization and secularism as a means to confront the obscurantist Islamist tide, both scholars use it as a starting point to discuss important issues in the context of their respective countries about the necessity to reform the current social, political, cultural, and intellectual stagnancy. They differ, however, in perceiving the extent of the discourse of secularism. Using the term “secularization” very carefully, Madjid makes clear that it should not be understood as leading to secularism in Indonesia. Unlike Madjid, Zakaria, inheriting the secularism debate from his predecessors, is more oriented toward rescuing secularism before it totally disappears in Egypt.